INTEGRASI USAHATANI DAN DIVERSIFIKASI KOMODITAS DALAM RANGKA PENANGGULANGAN DAMPAK KETERPURUKAN EKONOMI PASCA SERANGAN HAMA KELAPA Aspidiotus destructor DI KECAMATAN KEI BESAR KABUPATEN MALUKU TENGGARA - Hidayah, Ismatul (Badan Penerbitan Universitas Widyagama Malang, 2010)
Coconut crop is main cost of economics of public in district of Kei Besar Maluku Tenggara. But in the year 2002, pest raid Aspidiotus destructor at coconut crop causes ugly chartered investment counsel impact to public. Handling of chartered investment counsel social impact as result of depressed [by] it effort for plantation of coconut faces various constraints, between of knowledge and skilled of limited public and government programs that is unsatisfying comprehends sometimes not effective. This article aim to determine alternative of effort for agriculture in integrating farming and diversification [by] commodity for the planning of overcomes of economic depressing impact post coconut pest raid . Based on opportunity, local constraint and agroecosystem character, there is 12 alternative of effort for agriculture suggested, that is ( 1) Rejuvenation of Coconut In, ( 2) Farm of cashew, ( 3) Mix crop farming, ( 4) Pulses and feed forage, ( 5) Orange and Pineaple farm ( 6) Duck and native chicken farm ( 7) local cow farm ( 8) goad and sheep farm ( 9) Fishery of Demersal Rock, ( 10) Fishery of Lobster and crap, ( 11) Fishery of Small Pelagis, and ( 12) Fishery of Green Cockle. Â Key word : Farming integration, commodity diversification, Aspidiotus destructor